DEVELOPMENT OF STUDENTS’ WORKSHEET BASED GUIDED INQUIRY TO TRAIN SCIENCE PROCESS SKILL IN SIMPLE HARMONIC MOTION MATERIAL - RISMA MELATI, RINARTIKA; , MADLAZIM (Inovasi Pendidikan Fisika, 2018)
This present research aims at analyzing validity, practicality, and effectiveness of Students? Worksheet based guided inquiry to train students? skill of science process in simple harmonic motion material. This research is developing research using ADDIE model and it is compiled using One Group Pretest Posttest. The data collection techniques used were observation, questionnaire, and test. The data were analyzed through the implementation of learning, students? activity, students? responses, and students? test result of science process skill. The result of this research shows that: (1) the developed Students? Worksheet is valid in terms of guidance criteria, eligibility of content, procedures, and questions. (2) The developed Students? Worksheet is practical in terms of average score of learning implementation, students? activity observation, and questionnaire of students? responses that showed felicitous criteria. (3) The developed Students? Worksheet is effective in terms of the result of knowledge test and the skill of science process which has reached the percentage of classical mastery over 75%. Keywords: Science Process Skill, Guided Inquiry, Students? Worksheet.